Hartmann Southern Africa : keeping healthcare moving forward - van der Hoven, Chris; Townsend, Stephanie (London : Wits Business School, 2018)
The case outlines challenges opportunities for the Paul Hartman group, a supplier of medical, hygiene and healthcare products to expand into Sub-Saharan Africa.
Originally Published Invan der Hoven, C., & Townsend, S. (2018). Hartmann Southern Africa: Keeping healthcare moving forward. WBS-2018-4. Johannesburg: The Case Centre, Wits Business School.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Hartmann (Firm); Medical instruments and apparatus -- Africa, Sub-Saharan.; Hygiene products -- Africa, Sub-Saharan.